The Role of Parents in Enhancing Children’s English Skills: Evidence from Indonesia - Sri Wahyuningsih; Mohamad Ghufron Mua’dib (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2023)
In the globalization era, English has been an international language spoken by people throughout the world. To deal with this, English teaching has been conducted in educational sectors. Besides, parents play a main role in enhancing students’ English skills. The present study aims to elaborate on the role of parents in developing students’ English skills. This study is anchored in a qualitative case study method. The data were collected through semi-structured interviews with five Indonesian mothers aged 34 to 39 years. An interview guide was used as an instrument of the study to assist the authors during the process of the interview including support and roles provided by the parents in enhancing their English learning and some challenges they found. The findings reveal that Indonesian parents particularly mothers have roles in helping the success of their children’s English learning including facilitating children in accessing English learning resources, introducing English through daily interaction, facilitating children with English courses, and accompanying children in learning English at home. However, they also experienced some barriers to doing their roles such as the lack of knowledge in English, lack of English exposure in the community, and the need for being up to date with technological advancement. This study presents an implication that the need for parents to provide simultaneous efforts for enhancing a better linguistic environment at home and the need for collaborations from all aspects including school and society.